Efficient separation of strontium ions from aqueous solution by dibenzo-18-crown-6 functionalized resin: Static and dynamic adsorption studies with computational DFT insights - A.K. Singha Deb; M. Manju; A. Sengupta; Sk. M. Ali (Chemical Engineering Journal Advances, 2022)
The separation and utilization of radiotoxic 90Sr from liquid nuclear waste streams generated in the nuclear fuel reprocessing is highly desirable and challenging. Herein, we studied dibenzo-18-cown-6 functionalized chloromethyl-polystyrene (CMPS-DB18C6) resin which displays an excellent affinity toward Sr2+ion adsorption from aqueous solution. Adsorption behaviors were investigated as a function of solution pH, contact time, Sr2+ion concentration, temperature and presence of other metal ions. The prepared grafted resin exhibits high adsorption capacity of 141.37 mg/g at pH 6 with good selectivity in the presence of interfering coexisting ions such as Li+, Na+, Mg2+and Ca2+ions.The adsorption kinetics and isotherm were well fitted by the pseudo second order and Langmuir model, respectively. The adsorption efficiency was seen to be reduced with temperature. The regeneration of the used CMPS-DB18C6 resin was accomplished by 0.5 M HNO3acid and regenerated resin was reused up to four cycles with modest change in the adsorption capacity. The breakthrough curve analysis using a fixed-bed column showed 99.6% adsorber performance with bed capacity of 147.56 mg/g and 1.38 mbar pressure drop across the adsorber bed. The adsorbent showed good radiation stability as seen from the almost constant strontium distribution coefficient up to 500 kGy radiation dose. Further, the high adsorption and selectivity of Sr2+ ion was complimented using complexation Gibbs free energy by performing density functional theoretical calculations. The present work might provide an easy and efficient adsorptive removal process for the separation Sr2+ ions from radioactive waste stream for environmental remediation.